2011
DOI: 10.1136/gut.2010.214841
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow-derived mesenchymal stromal cells in the treatment of fistulising Crohn's disease

Abstract: Locally injected MSCs represent a feasible, safe and beneficial therapy in refractory fistulising Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
372
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(395 citation statements)
references
References 43 publications
8
372
0
15
Order By: Relevance
“…In CD, MSCs have been tested in clinical trials for two indications, namely fistulizing and luminal disease [38][39][40][41][42][43][44][45][46]. In fistulizing disease, the differentiation potential of MSCs is thought to be of crucial importance to achieve fistula tract closure.…”
Section: Msc and Ibdmentioning
confidence: 99%
“…In CD, MSCs have been tested in clinical trials for two indications, namely fistulizing and luminal disease [38][39][40][41][42][43][44][45][46]. In fistulizing disease, the differentiation potential of MSCs is thought to be of crucial importance to achieve fistula tract closure.…”
Section: Msc and Ibdmentioning
confidence: 99%
“…3 The use of MSC as a cellular therapy is currently being explored in clinical trials, including treatment of graft-versus-host disease, 4 promotion of engraftment following hematopoietic stem cell transplantation 5 and treatment of Crohn's disease. 6 The mechanisms underlying the immune suppression by MSC are still unclear. It has been widely shown that MSC suppress the proliferation of T cells upon allogeneic or mitogenic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…These studies assessed adipose‐derived stem cells in 143 patients. One phase I trial62 reported outcomes of mesenchymal stem cell treatment in 12 patients. Follow‐up in these studies ranged from 8 weeks to 24 months.…”
Section: Resultsmentioning
confidence: 99%